Visual element analysis in the packaging design of the Ataraksia Horror Series perfume using Gillian Rose's visual approach - Ardani, M. Widyan; Seknun, Akbar (Priviet Social Sciences Journal, 2026)
This study analyzes the visual elements of the Ataraksia Series Horor perfume packaging design, specifically the Peri Gandhamayit and Sanggar Hantu Laut variants, using Gillian Rose's framework of visual analysis (composition, modality, codes, and regime of truth). This qualitative approach aims to understand how elements such as dark colors, sharp serif typography, surreal illustrations, and symmetrical layouts interact to form a horror aesthetic, influence consumer perception, and build a strong brand identity. Primary data were collected through photographic documentation of the packaging and were analyzed descriptively and interpretively. The findings reveal that composition and modality create distorted visual horror narratives. Code analysis uncovers inspirations from local mythology (site of production) and the emotional responses of a gothic niche audience (site of audiencing). The regime of truth reinforces the brand's claim as a mystical cultural artifact that transcends mere fragrance. These findings offer theoretical implications for visual semiotics and practical implications for perfume design strategies.